Macadamia Nuts (Macadamia integrifolia) Value Chain and Technical Efficiency among the Small-scale Farmers in Zimbabwe - Bandason, Wellington; Parwada, Cosmas; Mushunje, Abbyssinia (Research on World Agricultural Economy, 2022)
Agriculture value chains are an indispensable tool for stakeholder collaboration, improving market access, foreign currency generation and increase in macadamia nut production in most developing countries. In Zimbabwe macadamia nut is a relatively new crop that has the potential to alleviate poverty and enhance livelihoods. Zimbabwe’s macadamia nut industry is still in its infancy and remains an under-researched area. Despite this, the technical efficiency of macadamia nuts production systems as proxied by production levels among small-scale farmers in the country is least understood. This study analyses the existing value chains by scrutinizing every step required in the production and marketing of macadamia nuts focusing on the technical efficiency of value chain nodes. The macadamia nut value chain in Zimbabwe is predominantly an emergency value chain system that does not embrace the modular value chain model and associated networks to enhance technical efficiency and overall welfare. The value chain system is characterised by imperfect market conditions with limited knowledge of exact specifications, attributes and prices of macadamia nuts. The existing value chain models for macadamia nut need to be re-aligned to accommodate all stakeholders, hence widening resource and knowledge-sharing platforms. There is a need for the Zimbabwe macadamia nut value chain to shift towards captive networks which embrace and scale out practices such as out-grower contractual arrangements. There is potential to design macadamia nut value chain models in Zimbabwe to increase the technical efficiency of the industry. ER